2006
DOI: 10.1357/002224006776412322
|View full text |Cite
|
Sign up to set email alerts
|

Constraining bubble dynamics and mixing with dissolved gases: Implications for productivity measurements by oxygen mass balance

Abstract: We used a dynamic mixed layer model to determine carbon export by the oxygen mass balance method from a time series of O 2 /Ar, N 2 /Ar and Ne measurements collected at station ALOHA near Hawaii from July 2000 to June 2001. The inert gas measurements constrain the flux of oxygen into the mixed layer from small, collapsing bubbles (injection) to be greater than or equal to the flux from larger bubbles (exchange), with mean estimates of the ratio in the range of 1-2. We also show that monthly observations of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
125
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 62 publications
14
125
1
Order By: Relevance
“…Additionally, the air injection flux can change dramatically with the wind speed (given the cubic dependence) and thus comparing estimates of air injection at different locations and times is difficult. The O 2 bubble flux estimated by Hamme and Emerson (2006) The partitioning between complete and partial trapping we calculate here is within the range of that predicted by Hamme and Emerson (2006). We found that in the winter, completely and partially trapped bubbles lead to significant contributions in the saturation anomalies of even soluble gases, suggesting that air injection may be more important than previously thought for soluble gases, such as CO 2 .…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Additionally, the air injection flux can change dramatically with the wind speed (given the cubic dependence) and thus comparing estimates of air injection at different locations and times is difficult. The O 2 bubble flux estimated by Hamme and Emerson (2006) The partitioning between complete and partial trapping we calculate here is within the range of that predicted by Hamme and Emerson (2006). We found that in the winter, completely and partially trapped bubbles lead to significant contributions in the saturation anomalies of even soluble gases, suggesting that air injection may be more important than previously thought for soluble gases, such as CO 2 .…”
Section: Discussionsupporting
confidence: 81%
“…In previous seawater studies, Ar has been used in conjunction with O 2 to estimate biological production (Craig and Hayward, 1987;Spitzer and Jenkins, 1989). Time-series of He, Ne and Ar measurements in seawater have been used to investigate air-sea gas exchange (Spitzer and Jenkins, 1989) as have time-series of Ne, Ar, and N 2 (Hamme and Emerson, 2006). Helium measurements in seawater have been used to investigate escape mechanisms for the exosphere (Bieri et al, 1967).…”
Section: Overview Of Approachmentioning
confidence: 99%
See 3 more Smart Citations